2022
DOI: 10.5430/wjel.v12n5p148
|View full text |Cite
|
Sign up to set email alerts
|

Hots Questions and Narrative Writing Ability of Lower Primary Pupils in a Vernacular School

Abstract: Narrative writing is a skill given emphasis by the Ministry of Education (MoE) through the specific Content Standards (CS) and Learning Standards (LS) stipulated in the Curriculum Standard and Assessment Document (DSKP) and aligned to the Common European Framework of References (CEFR) scales. However, lower primary pupils; particularly in urban areas still struggle to produce narrative writings that show quality. This paper presents and discusses an Exploratory Case Study on the use of Higher Order Thinking Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Earlier research also showed that digital storytelling helped improve how well learners could write stories. Studies discovered that digital storytelling got students more involved in narrative writing, which made them more creative and their stories more logically connected (Elizabeth et al, 2022;Tinialishel et al, 2023). This study added new information by looking at whether boys and girls benefited differently and paying attention to students who usually didn't do as well.…”
Section: The Overall Impact Of Digital Storytelling On Narrative Writ...mentioning
confidence: 99%
“…Earlier research also showed that digital storytelling helped improve how well learners could write stories. Studies discovered that digital storytelling got students more involved in narrative writing, which made them more creative and their stories more logically connected (Elizabeth et al, 2022;Tinialishel et al, 2023). This study added new information by looking at whether boys and girls benefited differently and paying attention to students who usually didn't do as well.…”
Section: The Overall Impact Of Digital Storytelling On Narrative Writ...mentioning
confidence: 99%
“…However, over the years, studies focusing on learners' writing skills in the English language have shown that their writing performances are still below expectations, particularly in the Malaysian ESL context. Malaysian students, in general, do not perform well in English language exams, particularly in the writing section (Azman, 2016;Xin-Li et al, 2022). Writing is seen as a cooperative effort rather than a solitary accomplishment (Gholami Pasand & Tahriri, 2017).…”
Section: Introductionmentioning
confidence: 99%